2013
DOI: 10.1039/c3fd20149j
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast ring-opening reactions: a comparison of α-terpinene, α-phellandrene, and 7-dehydrocholesterol with 1,3-cyclohexadiene

Abstract: The excited and ground state dynamics of a series of 1,3-cyclohexadiene derivatives and their hexatriene photoproducts are studied using ultrafast broadband UV-visible transient absorption spectroscopy. The substitution pattern around the cyclohexadiene backbone alters the excited state potential energy surface in the Franck-Condon region as evidenced by changes in the excited state absorption and fluorescence properties of the systems. Unsubstituted 1,3-cyclohexadiene and alpha-phellandrene exhibit no excited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…These measurements agree with the older experiments in most aspects. 79 The probe continuum does not reach the 0-0 transition of the tZt-HT isomer (Fig. 4), but the spectra are consistent with earlier studies over the region covered.…”
Section: Time-resolved Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…These measurements agree with the older experiments in most aspects. 79 The probe continuum does not reach the 0-0 transition of the tZt-HT isomer (Fig. 4), but the spectra are consistent with earlier studies over the region covered.…”
Section: Time-resolved Studiessupporting
confidence: 88%
“…6). 79 The studies by Marzec et al present the structural and thermodynamic properties of the open ring photoproducts, and use a conformation-sensitive analysis to show that the photochemistry of a-TP and a-PH consist exclusively of ringopening, with no signatures of a ''dewar'' form that can be found in other ring-opening reactions such as that of a-pyrone. 87,88…”
Section: A-terpinene and A-phellandrene Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…(10) The photochemical dynamics leading from the Franck-Condon region to the ring-opened photoproducts of αPH have been investigated by several ultrafast spectroscopic studies in both the gas and condensed phase, however largely without sensitivity to the structural dynamics, reactant conformers, or photoproduct isomers. (11)(12)(13)(14)(15) Here, we report on a combined megaelectronvolt ultrafast electron diffraction (UED) and ab initio multiple spawning (AIMS) (16)(17)(18) study of conformer-specific dynamics in the photochemical ringopening of gas-phase αPH with unambiguous conformersensitivity confirming but going far beyond the qualitative orbital-symmetry based WH rule predictions. In both our static diffraction measurements and quantum chemical calculations, we find the eq-αPH conformer to dominate in our gas phase sample (see supplementary note 1).…”
mentioning
confidence: 90%
“…70,71 More specifically, one can expect trend reversal when the range of conformational motion exceeds the size of the hydrogenbond cage in alcohol solvents, thereby leading to a higher enthalpic barrier. Such studies are underway and will be reported in a future publication.…”
Section: Resultsmentioning
confidence: 98%